Do Social Bonds Matter? Social Control Theory and Its Relationship to Desistance From Substance Abuse in China. (January 2021) - Wu, Guangzhen; Liu, Jianhong; Boateng, Francis D.; Cui, Shan; Shuai, Honglan
This study examines the effects of social bonds on drug users' desistance from substance abuse, with a special focus on testing the applicability of social control theory in the context of China. Using data from a sample of 419 Chinese drug users, this study reveals salient influences of such bonding variables as familial attachment, involvement, belief, and parenthood on drug users' confidence and efforts in achieving abstinence, providing some support for the arguments of social control theory. Given the limitations of institutional response in dealing with substance abuse issues, these findings have important policy implications for the direction of efforts to encourage desistance-related behavior among substance abusers.